Самовоспроизводящиеся белки, некоторые следствия и прогнозы - Кордюм, В.А. (Биополимеры и клетка, 1990)
Анализируется ситуация, сложившаяся в результате последних исследований прионов. Обосновывается предположение о том, что в дополнение к известной форме генетического кода в виде первичной последовательности нуклеиновых кислот существует вторая форма биологической информации — пространственная структура белка, способная к самовоспроизведению. Постулируется широкое распространение в клетках второй формы биологического кода как основы жизнедеятельности. Аналізується ситуація, що склалася в результаті останніх досліджень пріонів. Обгрунтовується припущення про те, що на додаток до відомої форми генетичного коду у вигляді первинної послідовності нуклеїнових кислот існує ще одна форма біологічної інформації – просторова структура білка, здатна до самовідтворення. Постулюється широке поширення в клітинах другої форми біологічного коду як основи життєдіяльності. The possible results of mutation identification in gene encoding protein, human priori precursor, under Gerstmann-Straussler syndrome are analyzed. The whole succession of events leading to appearance and following self-reproduction (just regardless of mutation gene now) of prions, a specific class of infectious proteins, has been formed up. The supposition that reproduction of alternative spatial structure underlies self-reproduction of infectious proteins whose existence was firstly predicted in 1969 by the author of this article, is stated and substantiated on the basis of existing information. It permits speaking about special form of protein code in the form of spatial structure enswing its self-reproduction in the same or similar spatial structure. Thus, in addition to the well-known form of genetic code as primary sequence of nucleic acids, the notion on the second form of biological information, i. e. spatial proteins structure able to self-reproduce, is introduced. A wide spreading of the second forms of biological code as a basis of vital activity in the cells is stated.